1999
DOI: 10.1159/000024280
|View full text |Cite
|
Sign up to set email alerts
|

The Recognition Pattern of Sequential B Cell Epitopes of Beta–Lactoglobulin Does Not Vary with the Clinical Manifestations of Cow’s Milk Allergy

Abstract: Background: β–Lactoglobulin (BLG) represents one of the major allergens causing cow’s milk allergy (CMA) – a disease with a wide spectrum of clinical symptoms. The aim of this study was to evaluate sequential B cell epitopes of BLG by the Pin–ELISA method. Furthermore, we wanted to investigate a possible association of the IgE recognition patterns in sera of patients with BLG sensitization and the type of clinical reactions following contact with cow’s milk. Methods: Overlapping sequential decapeptides corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 18 publications
1
24
0
2
Order By: Relevance
“…The hydrophilicity profile of the protein suggests that the antigenic site is at AA 124–134, which is on the surface of the protein and described as a major allergenic site in our study and those of other investigators [7, 9, 13]. AA 97–108 was described by Ball et al [10]as a major linear epitope, which corresponded to a major epitope (AA 95–113) also reported by Heinzmann et al [14], but not confirmed in our study or that of Williams et al [13]. Selo et al [12]reported the tryptic fragments AA 1–8, 25–40, 41–60, 102–124 and 149–162 as major IgE binding epitopes in a population of milk-allergic patients whose ages were not reported.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The hydrophilicity profile of the protein suggests that the antigenic site is at AA 124–134, which is on the surface of the protein and described as a major allergenic site in our study and those of other investigators [7, 9, 13]. AA 97–108 was described by Ball et al [10]as a major linear epitope, which corresponded to a major epitope (AA 95–113) also reported by Heinzmann et al [14], but not confirmed in our study or that of Williams et al [13]. Selo et al [12]reported the tryptic fragments AA 1–8, 25–40, 41–60, 102–124 and 149–162 as major IgE binding epitopes in a population of milk-allergic patients whose ages were not reported.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies that utilized digested peptide fragments or synthetic peptides have reported different findings with respect to the major sequential IgE binding regions on ALA [7, 8]and BLG [7, 9, 10, 11, 12, 13, 14]. In this study, we mapped sequential (linear) epitopes recognized by IgE and IgG antibodies using synthetic, overlapping decapeptides immobilized on a derivatized cellulose membrane and sera from patients with persistent CMA and those who are likely to outgrow their allergy.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this finding, we observed that the IgE binding capacity of tryptic-chymotryptic peptides of BLG was lower than for intact BLG. Although the major allergenic sites are located on the surface of the tridimensional structure of BLG, numerous highly reactive linear epitopes have been described (Ja¨rvinen, Chatchatee, Bardina, Beyer, & Sampson, 2001;Selo et al, 1998;Selo et al, 1999;Heinzmann, Blattmann, Spuergin, Forster, & Deichmann, 1999). These epitopes may become the target of intestinal microbiota, which has been shown to contribute to antigen degradation (Pessi et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The results are shown in Tables 1 and 2, where the peptide sequences obtained from the digestions were compared to b-lg fragments identified as epitopes by Sélo et al (1999) with different levels of immunoreactivity. Other studies have reported b-lg epitopes (Adams et al, 1991;Heinzmann, Blattmann, Spuergin, Forster, & Deichmann, 1999;Järvinen et al, 2001); however most of them are included in the epitopes described by Seló et al (1999). The number of identified peptides with previously described epitopes was lower for both CMP:b-lg 50:50 (14 and 16 at pH 7.0 and pH 3.5, respectively) compared to 28 and 32 in the b-lg digests.…”
Section: Mass Spectrometry Analyses (Hplc-esi-ms/ms)mentioning
confidence: 99%